Description of the pupal case of Anthrax midas Fabricius (Diptera: Bombyliidae: Anthracinae: Anthraciini), with the first host record for the species - Lamas, Carlos José Einicker; Soares, Matheus M. M.; Oliveira, Marcio Luiz De (Zootaxa, 2026)
The pupal case of Anthrax midas Fabricius, 1805 is described and illustrated for the first time. The examined material was reared from nests of Montezumia cortesia de Saussure, 1852 (Hymenoptera: Vespidae: Eumeninae: Odynerini), collected on a rural property in the municipality of Iranduba, within the Manaus Metropolitan Region, in the state of Amazonas, Brazil. This study also provides the first host record for A. midas.